Human rights law: international, Malaysian and Islamic perspectives - Hamid, Abdul Ghafur@Khin Maung Sein (Sweet and Maxwell Asia, 2012)
The book has been divided into three parts and consists of 24 chapters. Part I evaluates the nature, scope and effectiveness of the international legal framework for human rights. Part II is entitled “Malaysia and Human Rights: Traditions versus Universality”. It was supposed to be a comprehensive analysis of the Malaysian position in relation to the application of international human rights law and the contemporary human rights issues in Malaysia. The final Part of the book looks at human rights from Islamic perspective. In other words, this Part elaborates the position of Shari’ah (Islamic law) in respect of human rights.